Encapsulated betalains (Opuntia ficus-indica) as natural colorants. Case study: Gummy candies - Otalora Rodriguez, Maria Carolina (2019)
Gummy candies were selected as model food system to incorporate betalain-rich capsules (BC) obtained by ionic gelation with calcium alginate from a betalain-rich extract of Opuntia-ficus-indica fruit. Ten formulations were obtained by a factorial design (2 × 5) with two types of gelatin (GA and GB), and five betalain-rich capsules/gelatin (BC/G) ratios (from 70/30 to 30/70). The rheological and morphological properties of all formulations were studied, finding that the viscoelastic, gel strength, and stress relaxation properties were dependent on the G type content in the ratio BC/G. Optical micrographs also showed that G type, bloom, and BC/G ratio had a marked influence on the gummy candies structure. These data suggested that the G addition in higher concentrations allows to develop a more rigid gel. The betanin stability in the food system was evaluated during storage at 4 °C for 30 days and there was no significant variation in total colour parameters for all samples (ΔE ∗ values less than four). Thus, the stability of the betalain colour in the gummy candy was confirmed, exhibiting this food product a vivid red-purple colour, such representing a promising application for these natural pigments in food industry.